The Relationship between the Effectiveness of the #KerenTanpaNyampah Social Marketing Campaign and Green Brand Image Among @Thebodyshopindo.impact Instagram Followers - Wulandari, Arifah Aprilia; Anna Agustina; Mahmood, Zubair (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2024)
The social marketing campaign aims to achieve a social goal, one of which is an environmental issue. As known, the accumulation of waste is due to excessive use of plastic, leading to an increasing waste presence each year. In response, The Body Shop Indonesia endeavors to address this by strengthening its commitment to environmental issues through the #KerenTanpaNyampah campaign. The Body Shop utilizes Instagram as a platform to disseminate its social marketing campaign message. The campaign aims to foster a green brand image for The Body Shop in the eyes of its audience. The objective of this study is to examine the Relationship between the Effectiveness of the #KerenTanpaNyampah Social Marketing Campaign and Green Brand Image. This research adopts a positivist paradigm with a quantitative approach, conducted by distributing online questionnaires via direct messages to 376 followers of the @thebodyshopindo.impact Instagram account. The findings indicate a strong correlation between Variable X (Effectiveness of the Social Marketing Campaign) and Variable Y (Green Brand Image). Therefore, it can be concluded that the Effectiveness of the Social Marketing Campaign significantly and positively influences Green Brand Image.